PENGARUH PEMEKARAN KECAMATAN TERHADAP EFEKTIVITAS PELAYANAN DI KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - ", Nurhairoti; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Basically, every human being needs a service that could not be separated from eachindividual. The desire to get a good service is not only limited to rich or poor, young or old.All people want to get the best service. This is the basic reason of society at Koto KamparHulu District to do development. Society feel the services that was provided by the previousdistricts were no longer able to provide services as the society hope such as responsivenessto the needs of society. Too wide scope of work areas create district officials have been slowto respond the wishes of society who came to the district to do a variety of purposes. Most ofthem feel ignore due to long waiting queues but their problem could not be resolved quicklyby district officials. Therefore, by several communities societies who are now incorporated atKoto Kampar Hulu District who want to apply the proposal to do district development withhope the service in this area will be better after this developement are done.Then, the basic problem on this thesis is how the effect of district development toeffectiveness of public services at Koto Kampar Hulu District Kampar with the aim todetermine there are any influence of district development on the effectiveness of services, todetermine how much influence the district development of public services at Koto KamparHulu District Office, as well as to know how the influence of district development to publicservices at Koto Kampar Hulu District.The research found that there is a positive and significant effect betwen district developmentwith the effectiveness of public services at Koto Kampar Hulu District. It could be seen fromthe results obtained by calculating the correlation coefficient r count equal to 0.603 whichmeans that there is a relationship between the variable district development (X) with variableeffectiveness of public services (Y), and the degree of relationship is strong. Based ondetermination calculation, there is known that the influence of the district developement ofthe effectiveness of public services amounted to 60.3%. The Effect of district development toeffectiveness of public services is positive that can be tested by the formula Y = 511.49 +4,25X. This means that if the value of the variable X (district developement) increased by oneunit, then the value of the variable Y (the effectiveness of public services) will increase aswell.Keywords: District Developement, Services, and Influence